EFEKTIVITAS PENAMBAHAN EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa. L) TERHADAP AKTIVITAS ANTIOKSIDAN MINUMAN LIDAH BUAYA (Aloe vera) - Ahmad Fityan Ramadhan; Maya Sari; Anis Asmediana (Agroindustrial Technology Journal, 2018)
Aloe vera and rosella flower has high antioxidants and has the potential as a functional drink. The purpose of this study was to analyze the antioxidant activity of aloe vera drink with the addition of various concentrations of rosella extract and stored for 21 days. The results showed that aloe vera drink with the addition of rosella flower calyx extract had a significant effect on antioxidant levels. The addition of rosella flower calyx extract at a concentration of 3% has the highest antioxidant, which is 58.12% after being stored for 21 days. Increasing the concentration of rosella flower calyx extract also significantly affected pH and total acid values. Aloe vera drink with the addition of 3% rosella extract after storage of 21 days had a total acid value of 6.6% and a pH value of 3.86. Different results are shown in the analysis of sensory tests, where the addition of rosella flower calyx extract to aloe vera drinks did not significantly affect the reception of panelists.